Scratch test of pearlitic steels: Influence of normal load and number of passes on the sub-superficial layer formation. (December 2018) - Pereira, J.I.; Tressia, G.; Machado, P.C.; Franco, L.A.; Sinatora, A.
Abstract: The formation of sub-superficial deformed layer in pearlitic steels under dry sliding conditions has been widely researched, especially for the rail/wheel system. The RCF defects are considerate the most important feature to be analyze on the rail service life determination, being common practices, the employ of rail grinding procedure to remove the surface defects. In this work, the multi-pass scratch was used as the laboratory test simulating the material removal mechanism under wear-controlled conditions, observed in maintenance procedures on heavy railways (which correspond to multi-pass abrasive wear events). It was analyzed the microstructural transformation beneath the scratched surface as a function of the numbers of passes (i.e. one-pass to five-passes) and the constant normal load (i.e. 4 N and 8 N). The material of interest consisted in samples of pearlitic steel without prior work hardening. The features of the grooves were characterized by Coherence Correlation Interferometry (CCI) and Scanning Electron Microscopy (SEM). The White Etching layer (WEL) formation was characterized by Focused Ion Beam (FIB-SEM) and the crystallographic orientation was determined by Electron Backscatter Diffraction (EBSD). The characterization of the grooves features shows a small difference in the friction coefficient between test conditions not correlated by the geometrical aspects (variation up to 30% in depth and width). The SEM and FIB-SEM micrographs revels the WEL formation, consisted in a sub-superficial and transitional layer, characterized by ultra-fine grains and mixture of deformed pearlite colonies with undeformed colonies, respectively. Crystallographic texture can be found in samples tested with the lower normal load (4 N) and its relationship with the number of passes was determined as a function of the reference plane selected. The crystallographic texture to scratch direction (RD) was found in the less severe condition of passes, while in the transversal direction (TD) as a reference plane, a high concentration of pearlite colonies oriented at {111} was determined. Highlights: The use of multi-scratch test as a controlled abrasive test is proposed. The multi-pass test conditions promote the sup-superficial layer formation. High resolution microscopy was used in the microstructure characteristics. The crystal orientation influenced the sub-superficial formation.